Fourfold coordinated Te atoms in amorphous GeCu2Te3 phase change material - Jóvári, P.; Sutou, Y.; Kaban, I.; Saito, Y.; Koike, J. (Scripta materialia, 2013)
Amorphous GeCu2Te3 was investigated by X-ray diffraction and extended X-ray absorption fine structure measurements at the Ge, Cu and Te K-edges. Structural models were obtained by fitting the four experimental datasets simultaneously by reverse Monte Carlo simulation. It was found that Ge–Ge and Cu–Cu bonding are both significant. The average coordination numbers of Cu and Te, as well as Ge, are close to four. The high average coordination number of the network contributes to the enhanced thermal stability of amorphous GeCu2Te3.